2021
DOI: 10.1111/pan.14305
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ultrasound‐guided sacral intervertebral block for postoperative analgesia in neonates

Abstract: A sacrococcygeal teratoma and a sacral agenesis represent a contraindication to a caudal block. We report two cases where the optimal use of ultrasound helped place a sacral intervertebral catheter in two neonates. Radiological and ultrasound studies of the sacrum and spine should be available before performing the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 7 Another study reported two neonates with sacrococcygeal teratoma or sacral agenesis who were successfully placed with a sacral intervertebral catheter guided by ultrasound. 8 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Another study reported two neonates with sacrococcygeal teratoma or sacral agenesis who were successfully placed with a sacral intervertebral catheter guided by ultrasound. 8 …”
Section: Introductionmentioning
confidence: 99%